Anima(l) Moralia, or Righteous Anger: Agnieszka Holland’s Spoor - Elżbieta Ostrowska (Film-Philosophy, 2024)
Agnieszka Holland’s Spoor (Pokot, 2017), an adaptation of Olga Tokarczuk’s novel Drive Your Plough Over the Bones of the Dead (2009), tells the story of an old woman, Janina Duszejko (Agnieszka Mandat), who advocates for animal rights and uses every measure to fight the local hunting culture. Due to the centrality of the relationship between human beings and the world of nature, Holland’s film refers to the recent debates aimed at de-centralizing the human subject. This article will argue, however, that despite its attempt to alter the human–animal relationship, Spoor conveys anthropocentric perspectives and as such it does not participate in the “non-human turn.” Instead, the film can be linked to the “emotional turn” taking precedence in the humanities during the last two decades, in that it expresses the director’s affective response to the political realities of contemporary Poland, especially its unshaken patriarchal power, which subordinates the social margins.